Propuesta de un plan de negocios para la producción y comercialización de torta en el Distrito de Trujillo - Huanca Chayguaque, Katherin Liseth (2017)
The main objective of this thesis is to develop a market study that investigates assess the commercial and economic feasibility of a business plan for the production and marketing of cakes in the district of Trujillo, through description and explanation of its development, implementation and its results. The methodology I was used is the description of the business idea; formulation of a marketing plan; analysis of an operating plan; description of the administrative structure; Description of financial management and economic evaluation of the project. Rigorous information was collected and orderly manner, this involves recording and collecting data on the local environment. To this it was applied as a tool to the survey, which gave us a perspective of our target market; buying habits and consumer brand loyalty and purchase locations and allowed to get a glimpse of how customers react to new product. It was possible to determine the demand of cakes in the district of Trujillo, identify points for product distribution and marketing possible price. In addition, an advertising and promotion plan that allows positioning the brand in the market developed trujillano. Finally it was concluded that there is a great demand for cakes in the district of Trujillo, since the financial evaluation results: VAN E= S/. 722,627.72 and the TIR E= 330,71%. It is considered a viable and profitable business despite the growing presence of establishments that produce and market this product be based on the diet of trujillanos and with great acceptance.